Standpipe Systems for Fire Protection - Isman, Kenneth E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This important new manual goes beyond the published NFPA standards on installation of standpipe systems to include the rules in the International Building Code, municipal fire codes, the National Fire Code of Canada, and information on inspection, testing, and maintenance of standpipe systems. Also covered are the interactions between standpipe and sprinkler systems, since these important fire protection systems are so frequently installed together. Illustrated with design examples and practical applications to reinforce the learning experience, this is the go-to reference for engineers, architects, design technicians, building inspectors, fire inspectors, and anyone that inspects, tests or maintains fire protection systems. Fire marshals and plan review authorities that have the responsibility for reviewing and accepting plans and hydraulic calculations for standpipe systems are also an important audience, as are firefighters who actually use standpipe systems. As a member of the committees responsible for some of these documents, Isman also covers the rules of these standards and codes as they are written, but also provides valuable insight as to the intent behind the rules. A noted author and lecturer, Professor Isman was an engineer with the National Fire Sprinkler Association (NFSA), is an elected Fellow of the Society of Fire Protection Engineers (SFPE), and currently Clinical Professor in the Department of Fire Protection Engineering at University of Maryland.
Introduction to Standpipe Systems -- Types and Classes of Standpipe Systems -- Buildings Required to Have Standpipes -- Installation Rules for Hose Connections -- Installation Requirements for the Rest of the Standpipe System -- Hydraulic Calculations for Standpipe Systems -- Combined Sprinkler/Standpipe Systems -- Pressure Control in Standpipe Systems -- Pumps and Standpipe Systems -- High Rise Buildings -- Hanging, Bracing and Protection of System Piping -- Horizontal Standpipes and Lateral Piping -- Acceptance Testing of Standpipes -- Periodic Inspection, Testing and Maintenance -- Answers to "Test Yourself".
Keywords: Fire prevention; Buildings -- Protection; Security systems; Fire Science, Hazard Control, Building Safety; Security Science and Technology